2012
DOI: 10.3346/jkms.2012.27.11.1354
|View full text |Cite
|
Sign up to set email alerts
|

Onodera's Prognostic Nutritional Index as a Risk Factor for Mortality in Peritoneal Dialysis Patients

Abstract: The aim of this study was to evaluate the clinical relevance and usefulness of the Onodera's prognostic nutritional index (OPNI) as a prognostic and nutritional indicator in peritoneal dialysis (PD) patients. Patients were divided into 3 groups based on the initial OPNI score: group A (n = 186, < 40), group B (n = 150, 40-45), and group C (n = 186, > 45). Group A was associated with a higher grade according to the Davies risk index than the other groups. Serum creatinine and albumin levels, total lymphocyte co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…The Onodera PNI was originally proposed as a preoperative risk factor for gastrointestinal operation and a determinant of surgical indication in colorectal cancer but is now used widely as an indicator of nutritional assessment not only in the field of gastrointestinal surgery but also for the general hospital population. Perioperative nutrition status plays an important role in the incidence of postoperative complications [25,27,28] and on the overall survival after the resection of malignant tumors [15,[25][26][27][29][30][31]. A study also showed that PNI is an independent prognostic factor for overall and disease-specific survival in patients with gastric cancer [32].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The Onodera PNI was originally proposed as a preoperative risk factor for gastrointestinal operation and a determinant of surgical indication in colorectal cancer but is now used widely as an indicator of nutritional assessment not only in the field of gastrointestinal surgery but also for the general hospital population. Perioperative nutrition status plays an important role in the incidence of postoperative complications [25,27,28] and on the overall survival after the resection of malignant tumors [15,[25][26][27][29][30][31]. A study also showed that PNI is an independent prognostic factor for overall and disease-specific survival in patients with gastric cancer [32].…”
Section: Discussionmentioning
confidence: 89%
“…Hospitals that recognize the importance of nutritional therapy now have a nutrition support team, and the PNI is commonly used for their nutritional assessments [28][29][30]38]. This retrospective study has several limitations.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, an association between post-operative complications and depleted nutritional parameters has been reported following elective arthroplasty surgery [12]. Low lymphocyte or albumin counts are also predictive of mortality in ill health including renal dialysis [13,14] and cancer [15,16] as well as in the older population without apparent disease [17]. To our knowledge a similar relationship to fracture healing and fixation has not been previously investigated.…”
Section: Introductionmentioning
confidence: 79%
“…However, it is important to underscore that in critically ill patients this parameter can be changed by clinical status or the use of medication. Thus, OPNI seems to be better employed in patients receiving peritoneal dialysis, and those with terminal liver disease and active tuberculosis (10).…”
Section: ¹Mean ± Sd ²Median (Variation)mentioning
confidence: 99%
“…Low PA values are associated with morbidity and mortality in critically ill patients (9). OPNI, in turn, originally developed to predict prognosis in surgical patients, is a simple tool using measures of serum albumin and total lymphocyte Count (TLC) that can be rapidly applied in a large number of patients (10).…”
Section: Introductionmentioning
confidence: 99%